Learning Strategies through Apperception Riddles to Increase Concentration in Fifth-Grades Primary School Students - Putri, Ghina Fadillah; Muhroji, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research is motivated by the importance of providing apperception before learning because there are still many teachers in several schools who do not provide apperception before learning activities begin. With this, students feel they are not ready to receive lessons, so they cannot concentrate when studying. This research aims to describe students' responses after participating in learning, which begins with the apperception of riddles and the level of learning concentration of class V students at SD N 2 Kuwiran. This type of research is descriptive and qualitative. Data collection techniques use observation, interviews, and documentation. The data analysis technique uses interactive techniques, which consist of four activities carried out: data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the apperception of riddles can make students feel enthusiastic and happy when learning, which is shown by cheerful faces, good responses, and always paying attention to what the teacher says from beginning to end. Apart from that, students become more concentrated in studying and have a high level of concentration because they are able to fulfill six learning concentration indicators out of the seven existing indicators.